A note on the long-run neutrality of monetary policy: new empirics - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2013)
Economic theory traditionally suggests that monetary policy can influence the business cycle, but not the long-run potential output. Despite well documented theoretical and empirical consensus on money neutrality in the literature, the role of money as an informational variable for monetary policy decision has remained opened to debate with empirical works providing mixed outcomes. This paper addresses two substantial challenges to this debate: the neglect of developing countries in the literature and the use of new financial dynamic fundamentals that broadly reflect monetary policy. The empirics are based on annual data from 34 African countries for the period 1980 to 2010. Using a battery of tests for integration and long-run equilibrium properties, results offer overall support for the traditional economic theory.
Keywords: E51; E52; E58; E59; O55; 330; Monetary policy; Credit; Empirics; Africa